2019
DOI: 10.4103/jlp.jlp_173_18
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological profile and antibiotic susceptibility pattern of Gram-positive isolates at a tertiary care hospital

Abstract: OBJECTIVES: Gram-positive infections such as those by Staphylococcus aureus have contributed to the disease burden by increasing the morbidity and mortality rates in India. This study aims to determine the prevalence and the antibiotic susceptibility pattern of Gram-positive pathogens at a tertiary care hospital, Mumbai, Maharashtra, India. MATERIALS AND METHODS: This retrospective cross-sectional study was carried out from January, 2015 to December, 2017, at a tertiary care hospital in Mumbai, India… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
9
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 19 publications
6
9
1
1
Order By: Relevance
“…However, all our clinical isolates of S.aureus showed higher susceptibility to linezolid, vancomycin and teicoplanin (100% each). Similarly, higher susceptibility to linezolid (98%), vancomycin (98%), 9 and teicoplanin (98% )have been reported by others, thus emphasizing judicious use of these reserve drug in routine clinical 13 practice. Antibiotics like linezolid and vancomycin are the only alternative therapeutic agents for these MDR pathogens.…”
Section: Introductionsupporting
confidence: 55%
“…However, all our clinical isolates of S.aureus showed higher susceptibility to linezolid, vancomycin and teicoplanin (100% each). Similarly, higher susceptibility to linezolid (98%), vancomycin (98%), 9 and teicoplanin (98% )have been reported by others, thus emphasizing judicious use of these reserve drug in routine clinical 13 practice. Antibiotics like linezolid and vancomycin are the only alternative therapeutic agents for these MDR pathogens.…”
Section: Introductionsupporting
confidence: 55%
“…In the current study we report a prevalence of 67.3% in this hospital. Other studies have documented 20.3% of MRSA from Gujarat, 26.14% from Nepal, 29% from Mumbai and Mangalore, 53% from Pune and around 80% from Bubaneswar showing the varying prevalence of MRSA [15][16][17][18][19][20] . This wide variation in prevalence rate might be due to study design, inclusion and exclusion criteria, types of specimen, laboratory protocols, study duration, population included, phenotypic or genotypic characteristics studied etc.…”
Section: Discussionmentioning
confidence: 93%
“…Researchers have also reported varying level of resistance to clindamycin and doxycycline among MRSA. Gupta et al 6 in his studies reported 75.5% of MRSA isolates were resistant to clindamycin and in contrast, Mamtora et al 17 reported 73% of MSSA strains were resistant. In our study 50% of MRSA and 25% of the MSSA strains were resistant to clindamycin.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…On the other hand, they reported that resistance to vancomycin (34.0%) and teicoplanin (18.8%) was more frequent in E. faecium strains. Mamtora et al [11] reported that Enterococcus spp were highly susceptible to linezolid (96%), vancomycin (92%), and teicoplanin (93.3%) while being resistant to erythromycin and ciprofloxacin. Zallipour et al [12] reported the highest antibiotic resistance rates against tetracycline (93.5%), erythromycin (87%), and ciprofloxacin (80%) in E. faecalis isolates.…”
Section: Discussionmentioning
confidence: 99%